The Impact of the Agency Environment on Management’s Long-Term Focus - HUANG, Sterling Zhenrui (Institutional Knowledge at Singapore Management University, 2015)
The 1991 Credit Lyonnais court ruling expanded the fiduciary duties of managers towards debtholders in near-insolvent Delaware firms. Differences-in-differences tests reveal that innovation efficiency increased among all Delaware firms following the ruling. Further, Delaware firms close to (far from) insolvency reduced (expanded) their R&D expenditures and innovation output. Both sets of firms exhibit a reduced focus on meeting myopic earnings goals, and a shift from transient towards dedicated institutional owners. We conclude that expanding fiduciary duties towards debtholders motivated a longer-term focus at Delaware firms and, as evidenced by improvements in Tobin’s Q and solvency, benefited both shareholders and debtholders.